A Dynamic Area-Pressure Model Applied to Crystals in A Pot Plant Battery and Other Space Matter - Strömberg, Lena J. T. (ASEAN Journal for Science and Engineering in Materials, 2024)
Physical space, geometry, and matter are described with a theoretical formula, based on experimental results for a certain battery device. The model is derived from mechanical pressure on an area and applied for forming crystals. Those were found to develop in electrical devices, providing a spatial equivalent to the electrolyte. This study provides an explanatory model in some crystal formations as well as the optical reflections in terms of spectral activity.